The restoration of the Sistine Chapel (Citta del Vaticano Edizioni Musei Vaticani, 1994)
Gianluigi Colalucci, master restorer, and Carlo Pietrangeli, director-general of the Pontificial Academy of Science, recount their experiences in restoring Michelangelo's frescos in the Sistine Chapel.
VHS format.
Director, Luca de Mata ; narration, Robert Sommer ; music, Stelvio Cipriani ; scientific direction, Vatican Museums.
Keywords: Michelangelo Buonarroti, 1475-1564.; Cappella Sistina (Vatican Palace, Vatican City) -- Conservation and Restoration